The Impact of Trade Agreements in Latin America using the Synthetic Control Method - Hannan, Swarnali (IMF Working Papers; Working Paper ;, 2017)
The paper employs synthetic control method (SCM) to determine the impact of trade agreements for 64 Latin American country pairs in the period 1989-1996. The results suggest that trade agreements have markedly boosted exports in Latin America, on an average by 76.4 percentage points over ten years. However, there is variation across countries and agreements. The export gains due to trade agreements are lower than the world average comprising 104 country pairs in the period 1983-1995.